2018
DOI: 10.2147/cmar.s180695
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of derived neutrophil-to-lymphocyte ratio in surgical triple-negative breast cancer

Abstract: IntroductionThe role of derived neutrophil-to-lymphocyte ratio (dNLR) in predicting the prognosis of patients with triple-negative breast cancer (TNBC) has not been well studied. Here, we attempted to investigate the significance of dNLR in predicting the prognosis of patients with surgical (nonmetastatic) TNBC.MethodsA total of 281 patients diagnosed with surgical TNBC in The First Affiliated Hospital of University of Science and Technology of China from February 2005 to March 2015 were retrospectively includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
19
2
Order By: Relevance
“…This nding agrees with that from a previous study, which reported mdNLR values of 2.7 in TNBC cases and 2.4 in controls (3). A high NLR was associated with adverse survival of patients affected by various solid tumors, including TNBC (5,7,9,17). Howeverin contrast to the previous studies, mdNLR was not an independent predictor of OS in our study.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This nding agrees with that from a previous study, which reported mdNLR values of 2.7 in TNBC cases and 2.4 in controls (3). A high NLR was associated with adverse survival of patients affected by various solid tumors, including TNBC (5,7,9,17). Howeverin contrast to the previous studies, mdNLR was not an independent predictor of OS in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…For instance, an increased neutrophil-to-lymphocyte ratio (NLR) which is indicative of systemic in ammation, could promote cancer cell proliferation, angiogenesis, cellular migration, and metastasis (6). There is evidence from many studies for a prognostic role of NLR in peripheral blood of various cancer patients (7)(8)(9)(10), including breast cancer (8,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The presence and prognosis of systemic inflammation are increased by elevated C-reactive protein (CRP), leukocyte, platelet, ferritin and decreased albumin levels (9). Neutrophils, monocytes, and macrophages migrate to the site of inflammation, causing inflammation by releasing some cytokines and chemokines (8).…”
Section: Introductionmentioning
confidence: 99%
“…NLR measured before the start of neoadjuvant chemotherapy (NLR1) was the only independent prognostic serologic marker for prediction of survival. In previous neoadjuvant studies it has not been shown unequivocally that in TNBC NLR1 is an independent factor predicting survival (both DFS and OS) 9,11,14,19,20,21,22,23,24,25 ; however, a recent analysis of Bae et colleagues presented on a greater cohort this independent association 13 (Table 6). It was suggested that incorporating PLR may also be important predicting survival 26,27 .…”
Section: Discussionmentioning
confidence: 94%